Genotypic variation in yield, physiological traits, and drought tolerance of quinoa (Chenopodium quinoa Willd.) under arid conditions - Mousa, Magdi A. A.; Asiry, Khalid A.; Al-qurashi, Adel D.; Almasoudi, Najeeb M.; Elsayed, Mohammed I. (Frontiers in Plant Science, 2025)
Water scarcity is a major constraint to agricultural productivity in arid and semi-arid regions, underscoring the need for crops with high water-use efficiency and resilience to drought. This study evaluated 21 quinoa (Chenopodium quinoa Willd.) accessions under three drip-irrigation regimes—W1 (15 min), W2 (10 min), and W3 (5 min)—applied twice daily in a split-plot design with three replications in the arid conditions of western Saudi Arabia. Significant effects of irrigation, genotype, and their interaction were detected for most phenological, morphological, physiological, and yield traits. Among the evaluated accessions, CHEN-195, CHEN-316, and CHEN-140 consistently outperformed others, producing the highest seed yields per plant (up to 13.58 g) and per hectare (2400.2 kg ha-1), with greater 1000-seed weight and stable chlorophyll a and b contents across growth stages. Principal component analysis explained 70.7 % of the total variation, identifying yield, plant height, and drought tolerance indices as the principal contributors to genotype differentiation. Heatmap clustering confirmed distinct performance groups, reinforcing the robustness of multivariate classification in discriminating drought-adapted genotypes. The combined results highlight considerable genetic variability in quinoa response to irrigation levels and identify promising accessions with superior adaptation and resource-use efficiency. Overall, this study supports the integration of quinoa into dryland farming systems and provides a foundation for breeding programs targeting enhanced drought tolerance and sustainable production under water-limited conditions.